Autophagy Protects Against Developing Increased Lung Permeability and Hypoxemia by Down Regulating Inflammasome Activity and IL-1β in LPS Plus Mechanical Ventilation-Induced Acute Lung Injury - Nosaka, Nobuyuki; Martinon, Daisy; Moreira, Debbie; Crother, Timothy R.; Arditi, Moshe; Shimada, Kenichi (Frontiers in Immunology, 2020)
Targeting inflammasome activation to modulate interleukin (IL)-1β is a promising treatment strategy against acute respiratory distress syndrome and ventilator-induced lung injury (VILI). Autophagy is a key regulator of inflammasome activation in macrophages. Here, we investigated the role of autophagy in the development of acute lung injury (ALI) induced by lipopolysaccharide (LPS) and mechanical ventilation (MV). Two hours before starting MV, 0.2 mg/kg LPS was administered to mice intratracheally. Mice were then placed on high-volume MV (30 ml/kg with 3 cmH2O positive end-expiratory pressure for 2.5 h without additional oxygen application). Mice with myeloid-specific deletion of the autophagic protein ATG16L1 (Atg16l1fl/flLysMCre) suffered severe hypoxemia (adjusted p < 0.05) and increased lung permeability (p < 0.05, albumin level in bronchoalveolar lavage fluid) with significantly higher IL-1β release into alveolar space (p < 0.05). Induction of autophagy by fasting-induced starvation led to improved arterial oxygenation (adjusted p < 0.0001) and lung permeability (p < 0.05), as well as significantly suppressed IL-1β production (p < 0.01). Intratracheal treatment with anti-mouse IL-1β monoclonal antibody (mAb; 2.5 mg/kg) significantly improved arterial oxygenation (adjusted p < 0.01) as well as lung permeability (p < 0.05). On the other hand, deletion of IL-1α gene or use of anti-mouse IL-1α mAb (2.5 mg/kg) provided no significant protection, suggesting that the LPS and MV-induced ALI is primarily dependent on IL-1β, but independent of IL-1α. These observations suggest that autophagy has a protective role in controlling inflammasome activation and production of IL-1β, which plays a critical role in developing hypoxemia and increased lung permeability in LPS plus MV-induced acute lung injury.